Final answer:
To solve the equation 0 = x² + 6x + 13 by completing the square, follow these steps: Move the constant term to the right side of the equation, take half of the coefficient of x and square it, add it to both sides of the equation, factor the left side of the equation, take the square root of both sides, and solve for x.
Step-by-step explanation:
To solve the equation 0 = x² + 6x + 13 by completing the square, follow these steps:
Start with the equation: x² + 6x + 13 = 0
Move the constant term to the right side of the equation: x² + 6x = -13
Take half of the coefficient of x, square it, and add it to both sides of the equation: x² + 6x + (6/2)² = -13 + (6/2)²
Simplify: x² + 6x + 9 = -13 + 9
Factor the left side of the equation: (x + 3)² = -4
Take the square root of both sides: x + 3 = ±√(-4)
Solve for x: x = -3 ± ±√(-4)
Therefore, the correct answer is B. x = 3 + i√22 and x = 3 - i√22.